Reading Independently and Reading With a Narrator: Eye Movement Patterns of Children With Different Receptive Vocabularies - Su, Zhuqing; Wang, Yifang; Sun, Yadong; Ding, Jinhong; Ma, Zhuoya (Frontiers in Psychology, 2018)
This study examined the effects of two reading styles (i.e., reading with a narrator and reading independently), receptive vocabulary and literacy on children’s eye movement patterns. The sample included 46 Chinese children (aged 4-6 years) who were randomly assigned to two reading styles and read the same picture book on a screen. The results indicated that the higher the children’s receptive vocabulary, the sooner they fixated on the text. Overall, the children’s fixation probability (i.e., the time spent viewing the text zones as a proportion of full-page viewing time during each period) decreased with time when reading independently but increased with time when reading with a narrator. For children in senior kindergarten, reading with a narrator is thought to help establish and consolidate the links between speech and text and thus promote reading acquisition.